Clinical and Functional Outcome of Cervical Degenerative Disc Disease after Operative Treatment at Dr. Soetomo General Hospital Surabaya In 2013-2018 - Reyner Valiant Tumbelaka; Dwikora Novembri Utomo; I Ketut Martiana (Universitas Muhammadiyah Surabaya, 2021)
Backgrounds: Cervical degenerative disc disease is a pathological change in the cervical associated with the degenerative process. Surgery is one of the therapeutic modalities in cases of cervical degenerative disc disease. Post-surgical clinical outcomes are needed to evaluate the results of the actions that have been taken. Methods: This study is an observational retrospective study to evaluate clinical and functional outcomes using Neck Disability Index & SF36 on cervical degenerative disc disease before and after surgery at Dr. Soetomo Hospital Surabaya in 2013-2018. Data is processed using SPSS and compared using the T-test. Results: A total of 12 patients with details of 8 male patients and four female patients who met the inclusion and exclusion criteria in this study. There was a significant decrease in the average NDI score (p = 0.05) before surgery (47.33) compared with after surgery (15.58). There was a significant increase in the average SF36 score (p< 0.05) before surgery (50.75) compared to after surgery (88.16). Conclusions: There is an increase in clinical and functional outcomes in patients with cervical degenerative disc disease who undergo operative treatment.